Perubahan Perilaku Pemilih (Voting Behaviour) Partai Politik Islam Dalam Sejarah Kofigurasi Politik Indonesia - Ahmad Gelora Mahardika; Sun Fatayati (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2019)
This paper aims to examine the phenomenon of the decline of voters in Islamic ideology in Indonesia. Indonesian history notes that Islamic Political Parties have triumphed in political circles with their ability to impose fierce debates against nationalist groups and religions other than Islam when discussing constitutional changes. The endless debate then forced President Soekarno to issue a presidential decree. The sweet history of Islamic Political Parties began to decline when the regime of the New Order government fused authoritatively and caused no more unity of opinion in the Islamic party. At present, Islamic ideology political parties also have a tendency to turn to the Cacth All Party, which is considered more profitable and provides wider opportunities to gain power. This paper aims to prove the changing behavior of voters of Islamic political parties in the history of Indonesia's political configuration.